EVALUATION OF IN VITRO FERTILITY OF SEMEN FROM YOUNG LOCAL BULLS IN OOCYTES FROM OVARIES OF SLAUGHTERED ANIMALS - Cabrera V., Próspero (2009)
This study was carried out in the Center of Research and Instruction in Embryo Transfer (CIETE), sponsored by a partnership between the National Agrarian University of La Molina (UNALM) and the Ministry of Agriculture (MINAG), located at the UNALM campus. The objective was to evaluate the fertility and in vitro production of embryos of four bulls from the National Semen Bank. This study used 1031 oocytes of quality A and B obtained from ovaries of the local slaughterhouse. The oocytes were matured in the TCM-199 medium. The Percoll gradient centrifuge method was used for spermatic separation; sperm capacitation and fertilization was done in the TALP-IVF + PHE medium; and embryos were cultured with the Sofaa medium containing 5% Fetal Bovine Serum (FBS). Embryos were evaluated on days 7, 8, and 9 after fertilization. There were no statistical differences among the four bulls, and the fertilization rate was 63.3, 56.8, 68.8 and 72.9% for each bull. There was no statistical difference in the production of embryos between bulls. It is concluded that the bulls tested were in the normal range for in vitro embryo production.